Possible protective effect of remifentanil against testicular ischemia-reperfusion injury - Kölükçü Vildan; Unsal Velid; Katar Muzaffer; Balta Mehtap Gürler; Tapar Hakan; Karaman Tuğba; Karaman Serkan; Fırat Fatih; Yalçın Kenan; Gevrek Fikret; Kuyucu Yunus Emre (Türk Biyokimya Dergisi)
This study aims to evaluate the protective efficacy of remifentanil against testicular ischemia-reperfusion injury.